Sekolah Bahagia, Anak Sejahtera: Sinergi Lingkungan dan Pendidikan - Alma Nurkhoyah; Risbon Sianturi; Taopik Rahman; Farras Nur Arifah; Mia Ayunita; Nazwa Alifia Agustine; Nazwa Alifia Agustine (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Children's well-being in the school setting is an essential basis for successful holistic development. The purpose of this project is to examine how educational techniques and the physical and psychosocial school environment can work together to achieve long-term child well-being. This study's methodology is a descriptive literature review that looks at a variety of educational psychology and child-friendly school research journals. The findings demonstrate that children's sense of security and belonging is greatly increased when a warm teaching approach is combined with an inclusive physical setting and a supportive psychosocial climate. The study's conclusion highlights that a "Happy School" is attained when the school ecosystem can include elements of happiness into the curriculum and everyday interactions, which eventually lowers academic anxiety and raises student involvement. The implications of this research are twofold: theoretically, it enriches the discourse on child well-being by integrating ecological and pedagogical perspectives; practically, it provides actionable guidance for educators, school administrators, and policymakers to design child-centered environments and training programs that prioritize emotional safety alongside academic goals, ultimately contributing to more sustainable and inclusive educational practices